2020
DOI: 10.1371/journal.pone.0234968
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing conservation planning for multiple cohabiting species

Abstract: Conservation planning often involves multiple species occupying large areas including habitat sites with varying characteristics. For a given amount of financial resources, designing a spatially coherent nature reserve system that provides the best possible protection to targeted species is an important ecological and economic problem. In this paper, we address this problem using optimization methods. Incorporating spatial criteria in an optimization framework considering spatial habitat needs of multiple spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 39 publications
(50 reference statements)
0
7
0
Order By: Relevance
“…In our previous work where the same area and species were used in the empirical application (Dissanayake et al, 2014;Wang et al, 2020), we incorporated the dependency of the GFs on GT burrows when targeting to conserve these two species. In this paper, we emphasized the importance of considering this interspecies dependency and showed that the results could be dramatically different if this dependency was ignored (compare panel A with panels B and C in Figure 2).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our previous work where the same area and species were used in the empirical application (Dissanayake et al, 2014;Wang et al, 2020), we incorporated the dependency of the GFs on GT burrows when targeting to conserve these two species. In this paper, we emphasized the importance of considering this interspecies dependency and showed that the results could be dramatically different if this dependency was ignored (compare panel A with panels B and C in Figure 2).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…We note, however, that spatial contiguity is a difficult issue to address in an optimization framework. Although a few alternative modeling approaches have been presented in the literature (see, e.g., Wang et al, 2020), those approaches suffer from computational inefficiency. In general, MIP models become difficult to solve to exact optimality as the model size becomes larger.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although many conservation and restoration plans attempt to optimize benefits for a suite of native species (Wang et al. 2020), doing so successfully requires an understanding of the extent to which demographic responses are generalizable.…”
Section: Introductionmentioning
confidence: 99%
“…It is critical to identify what factors have similar effects on co-occurring species to inform community-wide management in the face of climate change. Although many conservation and restoration plans attempt to optimize benefits for a suite of native species (Wang et al 2020), doing so successfully requires an understanding of the extent to which demographic responses are generalizable.…”
Section: Introductionmentioning
confidence: 99%